2021
DOI: 10.1007/s10639-021-10602-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the use of digital technology in mathematics education

Abstract: Once the COVID-19 crisis is over, will everything” return to normal” or will we instead witness an ongoing boom in online learning? A time of crisis is an opportunity for all education systems to look to the future; there is enormous potential for digital technology in mathematics education, regardless of the impact of COVID-19. In this paper, the researcher focuses on answering two research questions: (1) Is COVID-19 the gateway for digital learning in mathematics education? (2) What type of digital technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 25 publications
6
36
0
14
Order By: Relevance
“…As shown in Tables 2 and 3 , PMTs assigned functions to technologies for the reorganization of classroom environments, of mathematical work in the classroom, and sometimes to recreate activities of conventional pre-pandemic teaching. This shows differences between technology agency as assigned by PMTs and its potential as documented for research in pre-pandemic teaching (Villa-Ochoa & Suárez-Téllez, 2021 ; Hillmayr et al, 2020 ; Erens & Eichler, 2018) and during the pandemic (Alabdulaziz, 2021 ; Naidoo, 2020 ). Similarly to results reported by Alabdulaziz ( 2021 ) and Naidoo ( 2020 ), in our study, the PMTs recognized that the pandemic created conditions for technology to remain in the educational process permanently; however, unlike these studies, our results reinforce the need to transcend a simple positive perception and to recognize the agency of technology and how it could be integrated into curricula and school context conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Tables 2 and 3 , PMTs assigned functions to technologies for the reorganization of classroom environments, of mathematical work in the classroom, and sometimes to recreate activities of conventional pre-pandemic teaching. This shows differences between technology agency as assigned by PMTs and its potential as documented for research in pre-pandemic teaching (Villa-Ochoa & Suárez-Téllez, 2021 ; Hillmayr et al, 2020 ; Erens & Eichler, 2018) and during the pandemic (Alabdulaziz, 2021 ; Naidoo, 2020 ). Similarly to results reported by Alabdulaziz ( 2021 ) and Naidoo ( 2020 ), in our study, the PMTs recognized that the pandemic created conditions for technology to remain in the educational process permanently; however, unlike these studies, our results reinforce the need to transcend a simple positive perception and to recognize the agency of technology and how it could be integrated into curricula and school context conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The Covid-19 pandemic has made the world educational institutions to conduct learning online [31], [32]. This situation made Indonesia stop the national examinations, causing each school to prepare its final examination items for determining the students' graduation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Alabdulaziz (2021) found that in Saudi Arabian mathematics education, mobile technologies, pen tablets and touchscreens had become popular hardware; and computer algebra systems, digital libraries and massive open online courses had become popular software. In American and British literacy education, there are cases where audiovisual recording and editing software and annotation software have become popular to support new practices such as virtual journaling and multimodal texts (Chamberlain, Lacina, Jimerson, Payne & Zingale (2020).…”
Section: Digital Literacy: Schooling Contextsmentioning
confidence: 99%